Risk Factors Contributing to Extrauterine Growth Restriction in Very Low Birth Weight Infants - Hye Su Hwang; Mi Lim Chung (Korean Society of Neonatology, 2024)
Purpose Despite advances in neonatal care, extrauterine growth restriction (EUGR) remains common in preterm infants. This retrospective single-center study aimed to determine the incidence and risk factors of EUGR in very low birth weight (VLBW) infants. Methods Data were collected concerning VLBW infants with gestational age (GA) <32 weeks between 2011 and 2020. EUGR was defined as a decline in weight z-score >1.2 from birth to discharge, using Fenton growth charts. Results Among 331 eligible preterm infants, the prevalence of EUGR at discharge was 71.6%. Infants with EUGR had lower GA and birth weight than those without EUGR. They also underwent prolonged durations of parenteral nutrition, invasive ventilation, and hospitalization. Neonatal morbidities, such as bronchopulmonary dysplasia, patent ductus arteriosus, necrotizing enterocolitis, gastrointestinal surgery, sepsis, and parenteral nutrition-associated cholestasis were more prevalent in the EUGR group. Multivariate analysis identified lower GA and longer time to reach full enteral feeding as independent risk factors, whereas maternal use of antenatal steroids and history of gestational diabetes mellitus were independent protective factors for EUGR. Conclusion As VLBW infants are at a high risk of EUGR, continuous attention and efforts to achieve early full enteral nutrition are required to decrease the incidence of EUGR.